Power compensation by distributed generation - Mohd Hanaffi, Yaa'kob (2010)
In order to reduce electricity cost, together with improving the performance of distribution systems, it has to deal with the problem of power losses minimisation. Although losses in the system can never be entirely eliminated, they can be controlled and minimised in several ways for example by installing Distributed Generation (DG) and shunt capacitor. DG can reduce line losses, increase system voltage profile, and improve power quality of the system. The shunt capacitor can be improving the power factor if the installation DG affects the power factor of network system. In this thesis, the proposed method is tested on standard IEEE 14 bus system and the results of the simulation carried out using MATLAB. While, DIgSILENT software was used to simulate the 26-bus test system by. By adding the DG, the losses of the system will be reducing while it can stabilize the network system. Therefore, distributed generation has improved the overall system performance.